-3x-9=-0.88+8

Simple and best practice solution for -3x-9=-0.88+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x-9=-0.88+8 equation:


Simplifying
-3x + -9 = -0.88 + 8

Reorder the terms:
-9 + -3x = -0.88 + 8

Combine like terms: -0.88 + 8 = 7.12
-9 + -3x = 7.12

Solving
-9 + -3x = 7.12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + -3x = 7.12 + 9

Combine like terms: -9 + 9 = 0
0 + -3x = 7.12 + 9
-3x = 7.12 + 9

Combine like terms: 7.12 + 9 = 16.12
-3x = 16.12

Divide each side by '-3'.
x = -5.373333333

Simplifying
x = -5.373333333

See similar equations:

| -3v^2-5v+24=0 | | (3x-2)(4x+1)= | | 145=10x-8 | | 3A+2B=2C | | 3+2*4= | | 7x^2+16x+11=0 | | x^2+9x+22=8 | | 2-4x=3(2-3x) | | 2-4x=3(2-3) | | -2y=-4(0)+5 | | 8y=-4(0)+4 | | 0.008v-32333=72+-22x | | y=1.16(4)+7 | | 5(3X+2)+(X+1)= | | 4(0)+8y=4 | | 6x=1/36 | | y=2(-17.5)+8 | | 0.4x+4=3x-0.7 | | 3(2X+1)+2(X+6)= | | 3x-0.2=4-4x | | 1.2x-6=2x+8 | | 2x^3+4x^2+50=0 | | 8(14)= | | 3xy+9x+y+3= | | x^2-x-41=6x+3 | | 10p^2+9=249 | | -12x+8=-27x+1 | | (v+7)+u= | | 6(5Y+3)+5= | | 3x^2+24x-30=0 | | 5z^2-5z-10=0 | | (3+5A)+5= |

Equations solver categories